Identification of Endophyte in Figs Fruit (Ficus carica L.) Potentially as Antibacterial with 16s rRNA Marking Gene - Venita; Endang Sulistyarini Gultom (Proceeding International Conference on Religion, Science and Education, 2023)
Infectious diseases are still one of the causes of morbidity and mortality in the world. Infectious diseases are usually treated with antibiotics, but their irrational application and consumption can be dangerous. Bacteria will be resistant to these antibiotics. Utilization of endophyte bacteria can be used as an antibiotic. Endophytic bacteria are bacterial colonies that live in various plant tissues without causing various disease symptoms for the host plant. Several studies have shown that endophytic bacteria are able to produce the same bioactive compounds as their host plants due to coevolution or genetic transfer from the host plant to endophytic bacteria. “Tin” or Figs plants are one of the plants that can be used as a source of endophytic bacteria. Many people use Figs to treat asthma, bronchitis, dry cough, diabetes, cancer, coronary heart disease, gout, and osteoporosis. This study aims to isolate and identify species of endophytic bacteria from Figs (Ficus carica L.) which have the potential as antibacterial. Isolation of endophytic bacteria from Ficus carica fruit was carried out by growing bacterial colonies on starch agar and then selecting those colonies that had clear zones. Bacteria that produced clear zones were then chracterized and identified through gram staining and 16S rRNA molecular test. The results showed that there were 6 endophytic isolates that were successfully isolated, 2 isolates with high inhibition were then identified using BLAST analysis and phylogenetic tree analysis using the Neighbor-Joining method in the MEGA 11 application. The identification results showed that isolate E1 had 100% similarity with Kodamaea ohmeri and isolate E6 have 99% similarity with Bacillus cereus.